1940
DOI: 10.1037/h0054629
|View full text |Cite
|
Sign up to set email alerts
|

The role of head movements and vestibular and visual cues in sound localization.

Abstract: This is the terminology employed in paper II. In paper I, the term lateral angle refers to the complement of the angle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
282
1
3

Year Published

1953
1953
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(298 citation statements)
references
References 0 publications
12
282
1
3
Order By: Relevance
“…Previous research has indicated the importance of vision in the accuracy of auditory localization judgments (Jackson, 1953;Jones, 1975a;Wallach, 1940). The spatial coordination of these two senses has been shown in infants by both the visual orientation of newborns toward a sound source (Muir & Field, 1979;Wertheimer, 1961) and the sensitivity of slightly older babies to a discrepancy between the locus of the acoustic and visual image of an object (Aronson & Rosenbloom, 1971;Spelke, 1976).…”
Section: Queen's University Kingston Ontario Canadamentioning
confidence: 99%
“…Previous research has indicated the importance of vision in the accuracy of auditory localization judgments (Jackson, 1953;Jones, 1975a;Wallach, 1940). The spatial coordination of these two senses has been shown in infants by both the visual orientation of newborns toward a sound source (Muir & Field, 1979;Wertheimer, 1961) and the sensitivity of slightly older babies to a discrepancy between the locus of the acoustic and visual image of an object (Aronson & Rosenbloom, 1971;Spelke, 1976).…”
Section: Queen's University Kingston Ontario Canadamentioning
confidence: 99%
“…Hence, if listeners were only to use these binaural cues, then front-back confusions would frequently occur in which a source located in the front hemifield was mistaken for one located in the rear hemifield (or vice versa). In practice, human listeners rarely make front-back confusions because they also use information gleaned from head movements to resolve ambiguities [4,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The present theories seem to indicate that localiration in a complex integation of intensity, temporal, and phase differences at the two ears. Additional cues are probably present resulting from visual stimuli and/or proprioceptive muscle tonus (8). Observations have also been made that complex tones are more easily and reliably located than are pure tones.…”
Section: Inroduct Ionmentioning
confidence: 83%